Pemikiran Malik Bin Nabi Mengenai Problem Tamadun Dunia Islam Kini - Hj. Ab. Majid, Mohamad Kamil (Jurnal Usuluddin, 1995)
This article discusses ideas of a well known scholar, Malik bin Nabi, concerning the problems in the Muslim World.